Indigenous knowledge on disaster management understanding adaptation strategies of Aetas in Bihawo and Lakas Pamayanan in Botolan, Zambales - Fonseca, Kevin Constantine R. (2012)
The study aimed at knowing the indigenous knowledge system regarding natural hazard and disaster management of Bihawo and LAKAS Pamayanan Aetas in Botolan, Zambales. Using some techniques of participatory research action (PAR), the study showed the relationship of the presence or absence of disaster management to the resilience of both non-indigenous and indigenous communities in the municipality. By looking at the current state of disaster management in the municipality of Botolan, it was found out that there exist problems with the 'top-down' disaster risk management approach employed by the local government unit. This can be seen on the insufficient proper coordination between the municipal and barangay LGUs and the lack of regard to local context and needs. These in turn result to lack of preparedness which negatively affects local communities particularly the non-indigenous Barangays. In contrast, the Aeta communities of Bihawo and LAKAS Pamayanan have showed that the presence of their indigenous knowledge system proved to be an effective tool in their own disaster risk management. Despite all the socio-political changes and stresses that they experienced, they were able to adapt new knowledge without losing their indigenous identity.
Title from title screen.
Also in print available at the Main Library Filipiniana Thesis Section.
Thesis (B.A.) -- University of the Philippines, 2012.
Keywords: Disaster management; Risk assessment; Indigenous peoples -- Ecology